Transcriptomic Comparison Reveals Candidate Genes for Triterpenoid Biosynthesis in Two Closely Related Ilex Species - Wen, Lingling; Yun, Xiaoyun; Zheng, Xiasheng; Xu, Hui; Zhan, Ruoting; Chen, Weiwen; Xu, Yaping; Chen, Ye; Zhang, Jie (Frontiers in Plant Science, 2017)
Native to Southern China, Ilex pubescens and Ilex asprella are frequently used in traditional Chinese medicine. Both of them produce a large variety of ursane-type triterpenoid saponins, which have been demonstrated to have different pharmacological effects. However, little is known about their biosynthesis. In this study, transcriptomic analysis of I. pubescens and comparison with its closely related specie I. asprella were carried out to identify potential genes involved in triterpenoid saponin biosynthesis. Through RNA sequencing (RNA-seq) and de novo transcriptome assembly of I. pubescens, a total of 68,688 UniGene clusters are obtained, of which 32,184 (46.86%) are successfully annotated by comparison with the sequences in major public databases (NCBI, Swiss-Prot and KEGG). It includes 128 UniGenes related to triterpenoid backbone biosynthesis, 11 OSCs (oxidosqualene cyclases), 233 CYPs (cytochrome P450), and 269 UGTs (UDP-glycosyltransferases). By homology-based blast and phylogenetic analysis with well-characterized genes involved in triterpenoid saponin biosynthesis, 3 OSCs, 14 CYPs and 1 UGT are further proposed as the most promising candidate genes. The comparative analysis between two Ilex species using blastp and OrthoMCL method displays high sequence similarity. All OSCs and UGTs as well as most CYPs are classified as orthologous genes, while only 5 CYPs in I. pubescens and 3 CYPs in I. asprella are species-specific. One of OSC candidates, named IpAS1, was successfully cloned and expressed in Saccharomyces cerevisiae INVSc1. Analysis of the yeast extract by gas chromatography (GC) and gas chromatography–mass spectrometry (GC-MS) shows IpAS1 is a mixed amyrin synthase, producing α-amyrin and β-amyrin at ratio of 5:1, which is similar to its ortholog IaAS1 from I. asprella. This study is the first exploration to profile the transcriptome of I. pubescens, the generated data and gene models will facilitate further molecular studies on the physiology and metabolism in this plant. By comparative transcriptomic analysis, a series of candidate genes involved in the biosynthetic pathway of triterpenoid saponins are identified, providing new insight into their biosynthesis at transcriptome level.